PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE TERHADAP HASIL BELAJAR IPS (Studi Eksperimen Kuasi Siswa Kelas IV SD N Kelurahan Bukit Sileh Kecamatan Lembang Jaya) - Yetti Rahmawati; Zariul Antosa; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This quasy experimental research aim to know the influence of the implementation cooperative learning type word square toward social science learning result students of 4th grade kelurahan Bukit Sileh kecamatan Lembang Jaya. The design reseach used control group posttest only design. population this research was the grade four elementary school in kelurahan Bukit Sileh Kecamatan Lembang Jaya. The sampel this research was student four grade in SD N 12 Bukit Sileh as control group and students four grade in SD N 20 Bukit Sileh as experimental. The data were collected was the result of studying of social science. The obtained data were analyzed using test mann whitney. Fro,mthe analysis result test mann whitney obtained z count = 2,189 while z table = 1,96 at a significance leve; of 5 %. Based on the result of this research it can be concludent there was influence of implementation cooperative learning type word square toward social science learning result students four SDN Kelurahan Bukit.Keyword : Cooperative type word square model based on environment, social sciencelearning outcomes